6x+8=4(x+6)

Simple and best practice solution for 6x+8=4(x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+8=4(x+6) equation:


Simplifying
6x + 8 = 4(x + 6)

Reorder the terms:
8 + 6x = 4(x + 6)

Reorder the terms:
8 + 6x = 4(6 + x)
8 + 6x = (6 * 4 + x * 4)
8 + 6x = (24 + 4x)

Solving
8 + 6x = 24 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
8 + 6x + -4x = 24 + 4x + -4x

Combine like terms: 6x + -4x = 2x
8 + 2x = 24 + 4x + -4x

Combine like terms: 4x + -4x = 0
8 + 2x = 24 + 0
8 + 2x = 24

Add '-8' to each side of the equation.
8 + -8 + 2x = 24 + -8

Combine like terms: 8 + -8 = 0
0 + 2x = 24 + -8
2x = 24 + -8

Combine like terms: 24 + -8 = 16
2x = 16

Divide each side by '2'.
x = 8

Simplifying
x = 8

See similar equations:

| -2x^2-2x+26.01=0 | | 5g^2+40g+35=0 | | 6(x-3)+2=3x+3(-4+x) | | 4+9g=22 | | -6(3x-8)=6.3 | | 7x+4=4x-25 | | r^2=57 | | x^2=(2*3)+3 | | 15-2x=x-14 | | -2x+38=x+15 | | 2(2x+3)=-4(x+1)-2 | | -4-12=13+x | | 6x-7=3x+25 | | 125m-100m+43200=45675-200m | | 2(x+4)=8x+5-6x+3 | | 2j^2-j-3=0 | | 4(-3y+5)+5y=13 | | x=283 | | x^2-x-12.01=0 | | 48x+8x= | | 4x+20=9x-4x | | 4b+5=29 | | 4x+20=9x-4y | | 10b^2-78b-16=0 | | x^2-x-11.99=0 | | 0.18x+0.02(y+4000)= | | 3(0)-2b=18 | | .20(x+12)=25 | | 4(6y+2)-6=-2 | | -8x-1.2=-7x-14.7 | | 16-48+4= | | 2(9+24)=30 |

Equations solver categories